An electromyographic study of esotropia. Issue 3 (March 1981) - Mitsui, Y; Tamura, O; Hirai, K I; Akazawa, K; Ohga, M; Masuda, K
Abstract : Under general anaesthesia the eye position of esotropia generally moved divergently. When retrobulbar anaesthesia was added bilaterally, the eye position moved further in the same direction. In the electromyogram under general anaesthesia the 4 horizontal recti were silent in controls. In many cases of esotropia, however, both medial recti showed a considerable amount of discharge under general anaesthesia. When retrobulbar anaesthesia was superimposed on one eye, the discharge from its medial rectus tapered off and, reciprocally, that of the opposite eye increased. These facts may suggest that proprioception plays in the development of esotropia.